Introduction: The Participatory Turn in Urbanism - Maroš Krivý; Tahl Kaminer (Footprint)
This issue of Footprint examines the recent participatory turn in urban planning and urban design. It discusses the co-opting of participatory processes by planning departments, the systematic disregard of inequalities, and the empowering of the market resulting from the ‘anti-statism’ present in many participatory schemes.